Administration of a long-acting antipsychotic injection to a child while managing contraindicated polypharmacy interactions and transition between services. Issue 6 (14th June 2019) - Akram, Gazala; Mitchell, Fiona
Abstract : Second-generation antipsychotics are used to treat a variety of psychiatric symptoms and illnesses as well as the behavioural aspects of various neurodevelopmental disorders. However, there is reluctance in using second-generation long-acting injectable antipsychotics in child psychiatry services. We present a case of a 12-year-old child whose presentation and medication regime warranted the use of aripiprazole long-acting injection against a backdrop of potential CYP P450 enzyme interactions as a consequence of polypharmacy. The case also describes the difficulties encountered working across different health sectors and agencies and highlights the ongoing need for skills-based Continuous Professional Development for Child and Adolescent Mental Health Services-based nursing staff.